Diseases affecting wheat: tan spot - Moffat, Caroline; Santana, F. (Burleigh Dodds Series in Agricutural Science, 2018)
Tan spot is a major fungal disease of wheat worldwide and a significant economic challenge facing growers. Here, we summarise common disease management strategies, including cultural practices, fungicide control and varietal resistance. We review the host–pathogen interaction and genetics of disease resistance, and discuss current tan spot research as well as future research trends towards a long-term solution. We include an example of tan spot management in Brazil and present a case study of the successful adoption of effector-assisted breeding in Australia.